(untitled) (International Journal of Food and Nutritional Sciences, 2022)
North East India (NEI) is a place in the Himalayan region constituting by hills, mountains, plains, rivers, waterfalls, sanctuaries, forest reserves and so on with granary and scenic beauty in the eastern part of India having floras and faunas and assimilated with composite cultural traits, conjoining therein the celestial things of nature along with varied nature of food habits, different cultural activities and festive affairs and besides; free life-style of ethnic populations who have been living in this remotest corner of the land-locked areas. However, this place is very important in so far as the composite culture as well as the living pattern of easy-going of various innocent tribal and ethnic groups of people in this region is concerned, who have been deprived off the basic amenities of life bringing facilities as compared to all-India level. So, this research paper attempts to discuss some important issues pertaining to cultural traits and food habits of people to focus their importance in all-India demographic situation, their participation, vulnerability, growing demands and equal development with the forward States of India. Taking into account all such stocks, it is expected that the paper will reflect on the essential findings and recommendations with valuable suggestions and conclusion in sparkling and celebrated manner for the purpose of urgent need of developmental activities in this backward part of the country to keep pace with forward moving requirements.